Insensibilidade, espetacularização e banalização do sofrimento em contos: práticas de leitura e interpretação no nono ano do Ensino Fundamental - Flach, Sidnei Luiz (2024)
This research stems from the conviction that literature can contribute to humanizing people. Inserted in a school culture in which the literary text is commonly used as a pretext for unreflective metalinguistic activities or mere decoding, competing with modern technologies, in a society that values fast-food reading, practiced on social networks, it is up to the school to find ways to develop critical readings of the world and, to this end, the power of literature is an effective tool. The insensitivity that permeates human relationships has worsened as the vis-à-vis contact of yesteryear has been replaced by the virtual contact of social networks, where, all too often, the suffering of others is transformed into a spectacle to be consumed and appreciated, further exacerbating the lack of empathy and connection between people. In view of the above, this dissertation seeks to stimulate interest in reading in ninth grade classes by increasing reading proficiency in short stories that deal with insensitivity towards others, leading readers to question individual and social attitudes towards the pain of others. The proposed activities aim to increase students' autonomy in relation to the text, so that they feel they are also producers of meaning. The short story was chosen because of its brevity, which allows it to be read in its entirety in the classroom, and its intensity, because of the genre's capacity for synthesis and expressive power. The research was developed from an interpretive qualitative perspective, with a propositional character. The theoretical reflections on reading are based on authors such as Kleiman (2002) and Solé (2014); on interpretation in Jauss (1979), Iser (1999) and Eco (1994; 2015); on the short story in Poe (1993) and Cortázar (1974); on insensitivity in Sontag (2003) and Bauman (2014). After the theoretical considerations, a Didactic Unit is proposed, divided into six modules. The short stories chosen for their approach to the theme of human insensitivity will be used as the corpus of analysis: O monstro, Amanhã eu volto and O suicida, by Luiz Vilela; Uma vela para Dario, by Dalton Trevisan; Colinas como elefantes brancos, by Ernest Hemingway; and Angústia, by Anton Tchekhov.